Resiliensi Siswa Madrasah Aliyah (MA) X di Kota Surakarta - Marganingrum, Asifa Nuriah Marganingrum; Musslifah, Anniez Rachmawati; Ernawati, Sri (Universitas Muhammadiyah Sorong, 2025)
The development of science and technology in the era of globalisation requires students to have adequate adaptability and psychological resilience in facing academic and social pressures. Resilience is an important ability for students to survive, bounce back, and thrive from various difficulties they experience. This study aims to describe the resilience of Madrasah Aliyah (MA) students in Surakarta City based on their subjective experiences. This study uses a qualitative approach with a phenomenological method, involving seven MA students as key informants. Data collection was conducted through participatory observation and in-depth interviews. Data analysis was conducted using the Miles and Huberman model, which includes the stages of data reduction, data presentation, and verification-based conclusion drawing. The results of the study indicate that student resilience is in the good category, as demonstrated by their ability to regulate emotions, self-control, optimism, problem-solving skills, empathy, self-efficacy, and the ability to derive meaning and lessons from difficult experiences. Resilience in this study was measured using resilience indicators based on Reivich and Shatte's aspects, which were consistently demonstrated in the informants' narratives. Student resilience was also strengthened by the support of parents, teachers, and peers in dealing with academic and social pressures.